2013
DOI: 10.1093/nar/gkt064
|View full text |Cite
|
Sign up to set email alerts
|

Control of human adenovirus type 5 gene expression by cellular Daxx/ATRX chromatin-associated complexes

Abstract: Death domain–associated protein (Daxx) cooperates with X-linked α-thalassaemia retardation syndrome protein (ATRX), a putative member of the sucrose non-fermentable 2 family of ATP-dependent chromatin-remodelling proteins, acting as the core ATPase subunit in this complex, whereas Daxx is the targeting factor, leading to histone deacetylase recruitment, H3.3 deposition and transcriptional repression of cellular promoters. Despite recent findings on the fundamental importance of chromatin modification in host-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 77 publications
0
90
0
3
Order By: Relevance
“…This may reflect tegumentdelivered pp71-mediated Daxx degradation and the subsequent reaccumulation of Daxx at later time points (68). In both adenovirus (75) and EBV (51) infections, decreases in H3.3 association with viral genomes upon Daxx depletion correlated with increased viral transcription, again pointing to Daxx-mediated H3.3 deposition as a means to silence infecting viral genomes.…”
Section: Discussionmentioning
confidence: 96%
“…This may reflect tegumentdelivered pp71-mediated Daxx degradation and the subsequent reaccumulation of Daxx at later time points (68). In both adenovirus (75) and EBV (51) infections, decreases in H3.3 association with viral genomes upon Daxx depletion correlated with increased viral transcription, again pointing to Daxx-mediated H3.3 deposition as a means to silence infecting viral genomes.…”
Section: Discussionmentioning
confidence: 96%
“…In the U2OS cell, ATRX is not expressed due to the deletion of the gene (37). Recently it has been reported that ATRX functions together with Daxx as a negative regulator in Ad gene expression and that the expression of EGFPtagged ATRX can reconstitute the functional Daxx/ATRX complex in U2OS cells (38). Therefore, U2OS cells were first transfected with the expression vectors for EGFP alone or EGFP-ATRX and then infected with Ad5-GFP and subjected to IF analyses.…”
Section: Incoming Ad Genome Complexes Do Not Localize At Pml-nbs Durimentioning
confidence: 99%
“…Furthermore, we employed Daxx-depleted U2OS cells (78) to additionally diminish the repressive effect of the Daxx-ATRX chromatin remodeling complex. We observed that Sp100A stimulated transcription from the Ad promoters ϳ2-to 3-fold in both cell lines.…”
Section: Sp100 Depletion Promotes Ad Progeny Production and Early Virmentioning
confidence: 99%